ANATOMICAL DESCRIPTION OF MUSCLES IN THE HIND LIMB AND TAIL OF CEBUS ALBIFRONS - Quevedo U., Miriam (2009)
The objective of this study was to perform the anatomic description of the muscles located in the hind limb and tail of Cebus albifrons. Four adult monkeys older than 3 years of age and castrated were used. The animals were euthanized and embalmed; then, after six days, the dissection of the hind limb and tail was carried out. Muscles were described in comparison with the Rhesus monkey (Maccaca mullata). The pelvis and thigh, leg and foot region presented 18, 12 and 11 muscles respectively. Piriformis, peroneotibialis, peroneus digiti quarti and the opponens digiti hallucis muscles were not present. The tail region presented 10 muscles, a higher number as compared to the Rhesus.